2014
DOI: 10.5604/20834543.1112225
|View full text |Cite
|
Sign up to set email alerts
|

Selected medical and psychological factors and quality of life in cardiovascular patients

Abstract: czynniki psychologiczne i medyczne a jakość życia chorych na choroby układu krążenia. Med. Og Nauk Zdr. 2014; 20(2): 131-135. Streszczenie Wprowadzenie i cel pracy. Celem pracy było ustalenie związku pomiędzy szeregiem czynników a jakością życia chorych na choroby układu krążenia (ChUK). Do czynników tych zaliczono: czas trwania choroby (chorób) układu krążenia, liczbę rozpoznanych chorób układu krążenia, obciążenie genetyczne ryzykiem rozwoju chorób układu krążenia, obciążenie czynnikami ryzyka rozwoju chorób… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…By contrast, the authors of the study observed a statistically significant negative correlation between the assessment of the quality of life made using the SF-36 in the PCS domain and the time elapsed since myocardial infarction rS = -0.293; p = 0.039. All groups showed that the duration of illness decreased the quality of life the most in the dimension of comprehensive mental health (MCS) as well as in the areas of social functioning (SF) and mental health (MH) (p < 0.05) [15]. Dias et al, analysing the quality of life using the SF-36 questionnaire in a group of 278 patients treated in hospital for acute coronary syndromes found that worse mental health (MCS) in the follow-up was associated with female gender.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, the authors of the study observed a statistically significant negative correlation between the assessment of the quality of life made using the SF-36 in the PCS domain and the time elapsed since myocardial infarction rS = -0.293; p = 0.039. All groups showed that the duration of illness decreased the quality of life the most in the dimension of comprehensive mental health (MCS) as well as in the areas of social functioning (SF) and mental health (MH) (p < 0.05) [15]. Dias et al, analysing the quality of life using the SF-36 questionnaire in a group of 278 patients treated in hospital for acute coronary syndromes found that worse mental health (MCS) in the follow-up was associated with female gender.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, media content also has a big impact on the level of children's knowledge [117,118]. Regardless of the place of the study or the group of respondents, the most frequently mentioned source of knowledge was the internet, followed by television and then teachers [90,92,95,119]. This seems dangerous given the amount of contradictory and false information appearing in the media.…”
Section: Sources Of Knowledge Of the Influence Of Ethyl Alcohol On Th...mentioning
confidence: 99%
“…This data makes it clear that research to assess the level of involvement of doctors and health care professionals in educating the public about the impact of alcoholic beverages on human health should be constantly conducted. Importantly, research with the participation of school youth shows that more than half of the respondents do not feel the need to deepen their knowledge in the context of the negative effects of ethanol abuse, which may increase the risk of developing alcohol dependence [119].…”
Section: Sources Of Knowledge Of the Influence Of Ethyl Alcohol On Th...mentioning
confidence: 99%
“…The treatment of hypertension, due to its causes, requires pharmacological management, but equally the modification of the current lifestyle. This is very difficult as older people are reluctant to modify their habits, but it is necessary as it determines the maintenance of normal body homeostasis and determines normal blood flow [15].…”
Section: Introductionmentioning
confidence: 99%